2017
DOI: 10.1101/197673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lipid-protein interplay in dimerization of the juxtamembrane domains of epidermal growth factor receptor

Abstract: Transmembrane (TM) helix and juxtamembrane (JM) domains (TM-JM) bridge the extracellular and intracellular domains of single-pass membrane proteins, including epidermal growth factor receptor (EGFR). TM-JM dimerization plays a crucial role in regulation of EGFR kinase activity at the cytoplasmic side. Although the interaction of JM with membrane lipids is thought to be important to turn on EGF signaling and phosphorylation of Thr654 on JM leads to desensitization, the underlying kinetic mechanisms remain uncle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…7E, right). We have reported previously that Thr654 phosphorylation causes the JM-A dimer to dissociate in the presence of acidic lipids (Maeda et al, 2018;Maeda et al, 2022). This constitutes the negative feedback regulation of the EGFR kinase function.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…7E, right). We have reported previously that Thr654 phosphorylation causes the JM-A dimer to dissociate in the presence of acidic lipids (Maeda et al, 2018;Maeda et al, 2022). This constitutes the negative feedback regulation of the EGFR kinase function.…”
Section: Discussionmentioning
confidence: 95%
“…In silico and in vitro analyses have suggested that PI(4,5)P 2 is involved in the dimerization of EGFR (Abd Halim et al, 2015;Maeda et al, 2018;Maeda et al, 2022;Matsushita et al, 2013). The aggregation of PI(4,5)P 2 with EGFR in the plasma membrane may help to stabilize the dimers of EGFR after its association with EGF.…”
Section: Pi(45)p 2 Is Important For Stabilizing the Egfr Dimermentioning
confidence: 99%
See 1 more Smart Citation